Sporting talent in volleyball: A scoping review - Oliveira, J. R. de; Werneck, F. Z.; Bara-Filho, M. G. (Journal of Human Sport & Exercise, 2024)
The aim of this study was to investigate the available literature on sporting talent in volleyball, and critically analyse what else has been researched in the area, methodological approaches, knowledge gaps, and encouraging future research. The search strategy was carried out in four electronic databases (PubMed®, Scopus, SPORT Discuss and Web of Science) using the PRISMA-ScR methodology (extension for Scoping Reviews). 78 articles were included for the final analysis. Most studies analysed female athletes (56.4%), in a cross-sectional design (85.9%), with group comparison (60.3%), bivariate analysis (66.7%) and application of test batteries (91%) of anthropometric (62.8%) and physical-motor (56.4%) characteristics. There were few studies that adopted a multidimensional (20.5%) and retrospective/longitudinal approach (11.5%), evaluated psychological skills (7.7%), subjective coach analysis (25.6%), motor coordination (9%), maturation (9%) and sociocultural characteristics (5.1%). Thus, talent identification in volleyball generally uses batteries of tests to discriminate between skill levels, mainly using physical tests (anthropometric and physiological measures), but the evidence for their validity in predicting future performance and discriminating skill levels is limited. Future research should adopt multidimensional and longitudinal approaches, combining objective and subjective indicators of sporting potential of young volleyball athletes.